Prevalence and management of natal/neonatal teeth in cleft lip and palate patients - Yilmaz, R. Burcu Nur; Cakan, Derya Germec; Mesgarzadeh, Nasim (European Journal of Dentistry, 2016)
Objective: The aim of this study was to determine the prevalence and distribution of natal/neonatal teeth in infants with cleft lip and palate (CLP) according to gender, involving jaw and side and to show the management of some cases. Materials and Methods: A retrospective study was carried out on medical history and photographic records of 69 infants with CLP, who were treated at the CLP clinic of Yeditepe University between years 2014–2015. The presence of neonatal teeth was determined, and if present the gender, type of cleft, and position were recorded. Statistical analysis was performed. Results: Neonatal teeth were observed in 7% of the study group. No significant differences were found between cleft types and gender (P > 0.05). The prevalence of neonatal teeth in bilateral, unilateral and isolated cleft type was 16.5%, 6.5%, and none, respectively. All neonatal teeth were located in the maxilla and on the cleft-side (100%). Conclusion: The presence of natal/neonatal teeth in infants with CLP was not rare. In all of these cases the teeth were located adjacent to the cleft region. In isolated palatal cleft, where the alveolar region including the teeth buds are away from the cleft, no neonatal teeth were observed. It may be concluded that neonatal teeth in infants with CLP are frequently present and located inside the borders of the presurgical orthopedic treatment (POT) plate. Therefore, if possible, immediate extraction of the neonatal teeth is advised or if not possible because of systemic health reasons, modifications of the plate are required.
Keywords: Cleft lip and palate; natal/neonatal teeth; orthodontics